Open research data in human movement analysis: Swiss-initiated-guidelines for broader scientific communities - Michelle C. Haas; Bettina B. Sommer; Felix Moerman; Simon van Rekum; Eveline S. Graf (Data in Brief)
Sharing of data and code leverages transparency and reproducibility of data collection and analysis. However, in biomechanics, such sharing practices are still underdeveloped, possibly due to a lack of knowledge or support. Existing community standards as of today do not yet cover the entire data life cycle and are limited to reporting only one component of movement analysis such as kinematics, kinetics, or surface electromyography, rather than combining these elements. To address this gap, we developed comprehensive guidelines for reporting and sharing human movement data collected with various measurement systems. These guidelines were iteratively developed between January and June 2024, based on requirements which were informed by a survey and workshop within the scientific community. Survey and workshop results highlighted common data sharing practices among movement laboratories, but also significant challenges in standardizing formats, managing metadata, and navigating ethical and legal regulations. The resulting guidelines, structured along the data life cycle, provide detailed recommendations for each stage of the life cycle. Key recommendations include ensuring informed consent for data sharing, maintaining comprehensive metadata, using open formats, and selecting appropriate repositories. Unlike existing standards, which are typically specific to one measurement system, our guidelines integrate and extend upon these recommendations, emphasizing data sharing perspectives tailored to the Swiss and European legal frameworks. To facilitate reporting of metadata, templates are provided. By adhering to these guidelines, researchers can foster a more collaborative, transparent, and impactful scientific community in the field of human movement analysis.